Different effects of intravitreally injected ranibizumab and aflibercept on retinal and choroidal tissues of monkey eyes. Issue 6 (23rd January 2014) - Julien, Sylvie; Biesemeier, Antje; Taubitz, Tatjana; Schraermeyer, Ulrich
Abstract : Background: Since there is evidence that the Fc domain of antivascular endothelial growth factor drugs may cause unexpected consequences in retinal and choroidal vessels, the effects of intravitreal ranibizumab and aflibercept on monkey eyes were investigated. Methods: Four cynomolgus monkeys were intravitreally injected with 0.5 mg of ranibizumab and another four with 2 mg of aflibercept. Two untreated monkeys served as controls. Funduscopy, fluorescein angiography (FA), spectral-domain-optical coherence tomography (SD-OCT) and measurement of intraocular pressure (IOP) were performed. The eyes were inspected by light, fluorescence and electron microscopy. The diameter of the choriocapillaris (CC) was measured by morphometry, and the areas of the CC with free haemoglobin, CC fenestrations and endothelial thickness were quantified. Results: Analysis showed ranibizumab permeated the retina via intercellular clefts, whereas aflibercept was taken up by ganglion cells, cells of the inner and outer retinal layers and the retinal pigment epithelium (RPE). Stasis and haemolysis in the choriocapillaris and choroidal vessels were more frequent after aflibercept treatment, which caused hypertrophy and death of individual RPE cells. The area of the CC was significantly reduced after both drugs compared with controls, but the reduction of the CC endothelium thickness, number of fenestrations and the areas with haemolysis were more pronounced after aflibercept. Conclusions: Ranibizumab permeated the retina through intercellular spaces, whereas aflibercept was taken up by neuronal and RPE cells. Aflibercept induced protein complex formation and more haemolysis in the choriocapillaris, leading to individual RPE cell death. The clinical significance and relation of these findings to the Fc domain or to other characteristics of aflibercept remain to be investigated.